Spot Tests in Organic Analysis - Feigl, F.; Anger,V. (New York : Elsevier, 1972)
Annotation Covering all theoretical and practical aspects of the applications of spot tests to organic analysis, this book includes information on more than 900 tests. It continues to be an indispensable reference to organic and analytical chemists in academia and in industry.
Includes index.
Keywords: Spot tests (Chemistry); Chemistry, Organic